Differences in activity and stability drive transposable element variation in tropical and temperate maize - Ou, Shujun; Scheben, Armin; Collins, Tyler; Qiu, Yinjie; Seetharam, Arun S.; Menard, Claire C.; Manchanda, Nancy; Gent, Jonathan I.; Schatz, Michael C.; Anderson, Sarah N.; Hufford, Matthew B.; Hirsch, Candice N. (Genome Research, 2024)
Much of the profound interspecific variation in genome content has been attributed to transposable elements (TEs). To explore the extent of TE variation within species, we developed an optimized open-source algorithm, panEDTA, to de novo annotate TEs in a pangenome context. We then generated a unified TE annotation for a maize pangenome derived from 26 reference-quality genomes, which reveals an excess of 35.1 Mb of TE sequences per genome in tropical maize relative to temperate maize. A small number (n = 216) of TE families, mainly LTR retrotransposons, drive these differences. Evidence from the methylome, transcriptome, LTR age distribution, and LTR insertional polymorphisms reveals that 64.7% of the variability is contributed by LTR families that are young, less methylated, and more expressed in tropical maize, whereas 18.5% is driven by LTR families with removal or loss in temperate maize. Additionally, we find enrichment for Young LTR families adjacent to nucleotide-binding and leucine-rich repeat (NLR) clusters of varying copy number across lines, suggesting TE activity may be associated with disease resistance in maize.